Zein/PVDF micro/nanofibers with improved mechanical property for oil adsorption. (3rd February 2020) - Teng, Defang; Wahid, Abdul; Zeng, Yongchun
Abstract: Development of "green" oil sorbents with features such as high sorption capacity, eco-friendliness, and reusability is of great significance because frequent oil spill incidents have caused severe environmental concerns. In this study, zein, a natural protein extracted from corn, is introduced to be an attractive candidate as oil sorbent for the first time. However, the zein film has poor mechanical properties, which limits the broad application in reality. In this work, Poly(vinylidene fluoride) (PVDF) is introduced into zein fibers to produce oil sorbents with improved mechanical properties using bicomponent electrospinning. The new hierarchical structure of zein/PVDF fibers with helical ribbon morphology are reported. The formation mechanisms of ribbon fibers and helical fibers are involved in the explanation of the generation of this new hierarchical structure. This study demonstrates that micro-/nano-materials based on the natural proteins such as zein are promising materials for developing "green" oil sorbents. Graphical abstract: Image 10302 Highlights: The morphology of zein fibers transforms from rod to ribbon can be controlled by the solvent mixture and concentration. Ribbon zein fibers present excellent oil sorption capacity. Bicomponent electrospinning of zein and PVDF generates fibers with unique helical ribbon morphology. Combination of zein and PVDF improves the mechanical properties, oil retention and reusability of the zein-based film.